Materials takeoff in building information modeling - Muhammad Syaiful Safwan , Nordin (2015)
Appropriate cost estimation, monitoring and controlling are the key point of construction project td succeed. 2D drawing has been a normal source of information and procedure since 1970's. The drawback of drawing based estimating however is its nature where it has limited information that is required by the estimators. In addition, it also requires manual estimation and thus introduces inaccuracy and error in measurement. The source of inaccuracy and error comes from the estimator that needs to review many sheets of drawing for extracting building component and quantification measurement to perform materials takeoff. Therefore, more time is needed to establish unit measurement of the building component. Material takeoff in Building Information Modeling (BIM) is performing takeoff, counts and measurement of building components quantification by using parametric underlying 3D model instead of using conventional method for conducted manual materials takeoff for cost estimation. By performing takeoff, count and measurement by using parametric model instead of conventional method, all possible problems due to miscalculation and human error can be minimized. Besides that, by using BIM model based approach on estimating and materials takeoff, takeoff, count and measurement for quantification can be done quickly and more accurately. The scope of this is study is to perform takeoff, count and measurement by using BIM 3D parametric Architecture Model. The aim of this study is to explore the BIM model based approach on estimating and materials takeoffs. Research method that been used in this study is extracted all building component information about measurement, count and takeoff by using Revit Suite 2014 software as an input for conducting cost estimation. Finally, all the quantification takeoff extracted from parametric model is used for performing cost estimation of the architecture components of this bungalow construction. All the cost estimation is calculated by using Excel data sheet that have been developed by researcher. By using this BIM model approach, researcher believe that it will helps construction project teams for better project coordination in the coming years.